Did US Safeguard Protection on Steel Affect Market Power of European Steel Producers? - Hylke Vandenbussche; Ziga Zarnic (Katholieke Universiteit Leuven, LICOS Centre for Transition Economics, 2006)
This paper empirically investigates the effects of US safeguard protection on steel imports in 2002 on the mark-ups of EU steel producers. We identify a large panel of European steel producers between 1995 and 2004 affected by the safeguards. Using the Roeger method, our results show that US safeguards significantly reduced EU firms?mark-ups. Single-product EU steel firms suffered relatively more from the protection than multi-product firms. Controlling for firm heterogeneity, these results are robust to alternative specifications. Our evidence further suggests that US protection resulted in some rerouting of European steel especially towards China, aggravating the situation on the Chinese steel market and ultimately resulting in Chinese trade protection of steel imports.
Keywords: F13; L13; L61; 330; Firm data; Markups; Safeguards; Steel industry; Trade deflection; Außenhandelsbeschränkung; Stahlhandel; Außenwirtschaftspolitik; USA; Stahlmarkt; EU-Staaten